Orchidaceae Juss. no Parque Nacional do Iguaçu, Paraná, Brasil - Zubek , Hauanna (2023)
This study presents a taxonomic treatment of the Orchidaceae species in Iguaçu National Park (ParNa Iguaçu), Paraná, Brazil, one of the largest Atlantic Forest remnants in the state of Pa raná. Orchidaceae is represented in the area by 66 species, distributed in 42 genera, the most representative being Gomesa (7 spp.) and Acianthera (6 spp.). Representatives of three subfam ilies are present in ParNa Iguaçu, Vanilloideae (2 spp.), Orchidoideae (12 spp.) and Epiden droideae (52 spp.) which, as expected, presents the greatest richness (81% of the total). Among the species found, six are considered endemic to Brazil, 25 are endemic to the Atlantic Forest (36%) and one is endemic to Paraná (Acianthera violaceomaculata (Hoehne) Pridgeon & M.W. Chase). Thirty-two new records were found for the area. Regarding the vegetational formations, the areas of Mixed Ombrophilous Forest had 29 exclusive species, while the Semideciduous Seasonal Forest had 21, while, 16 species occur in both phytophysiognomic formations. Two new occurrences were registered for the Mixed Ombrophilous Forest and one new occurrence for the Semideciduous Seasonal Forest. Regarding the conservation status of the species, only 18 have been evaluated as to the degree of threat, with 15 classifieds as of Least Concern and three classifieds as Vulnerable. Regarding habit, epiphytic was the most representative (39 spp.), followed by terricolous (15 spp.) and two mycoheterotrophic species. Among the families already inventoried in ParNa Iguaçu, Orchidaceae is among the richest and the findings of the present study reinforce the importance of floristic studies for cataloging the local flora.